Cancer incidence in the districts of Wielkopolska, 1999-2001. Indirect method of standardization - Wojtyś, Piotr; Gryczka, Robert; Godlewski, Dariusz (Contemporary Oncology/Współczesna Onkologia, 2005)
The analysis of health problems in oncology is based on an appropriate description of the epidemiological situation. The analysis is difficult when the population and the number of cases per year are small. In this work, in order to determine the cancer incidence in the districts of Wielkopolska the indirect method of standardization was used. The number of cancer cases was obtained from the Regional Cancer Registry in Poznań, the data about the age structure were obtained from the Provincial Statistical Office in Poznań. The analysis was made for all cancers for both sexes and for the most frequent cancers (with the exception of the skin) in men (lung, colorectal, prostate) and women (breast, colorectal, lung). For the particular SIR (Standardized Incidence Ratio) the 95% confidential interval was counted. The highest cancer incidence in women was observed in the city districts and in the Piła district, while in men the highest incidence was observed in the northern and north-western Wielkopolska. Breast cancers in Wielkopolska were the most frequent in the Poznań district and in the Międzychód district. The highest lung cancer incidence in men was observed in the northern part of the region. The indirect method of standardization is more resistant (than the direct one) to the influence of the sampling variation. Additionally, to reduce the influence of the random variability the number of cases from three years was cumulated.